Reflections on the renewed significance of Huguenot thought - Charles, Marie P. (Koers, 1983)
Traditional Huguenot values might be usefully employed in the planning of political objectives for the future. In rejecting the views which have rendered wan a mere object, a new form of spiritual humanism is advocated. In contrast to the merely “structural'' and the “communicative” a form of philosophy which allows for an essentialist participation should be encouraged. The present situation in South Africa, within the framework o f post-colonial Africa, is discussed, and certain parallels drawn between the Afrikaners and the bourgeoisie in France following the Revolution of 1789. It is pointed out that the Afrikaner “bourgeois” people can be regarded as being perhaps the only remaining bourgeois people still in a progressive period o f their civilization. This makes them a powerful force. The question now to be considered is to what extent the labouring classes could be drawn into the mainstream - and it is not impossible that this could be achieved without upheaval if old Huguenot values were to be respected. Certain writers like Ellul, Brun, and Aron suggest creatively ways in which, in contrast to the Saussurean principle of the arbitrariness of the linguistic sign, forms of unity may be attained. The arbitrariness of the linguistic sign and its consequences should be avoided at all levels. It is therefore suggested that the original Huguenot values could help contemporary scholars and politicians lo plan ahead in a deductive rather than an inductive n a y for a more just and credible future. What has to be sought, as had been the ease with Calvin too, is the deduction of Cod rather than the inductions of man.